Actin polymerization in neutrophils from donors of peripheral blood stem cells: Divergent effects of glycosylated and nonglycosylated recombinant human granulocyte colony‐stimulating factor - Carulli, Giovanni; Mattii, Letizia; Azzarà, Antonio; Brizzi, Stefania; Galimberti, Sara; Zucca, Alessandra; Benedetti, Edoardo; Petrini, Mario (American journal of hematology, 2006)
Neutrophil functions can be modified by Recombinant human G‐CSF (rhG‐CSF) treatment, with divergent effects on phagocytosis, motility, bactericidal activity, and surface molecule expression. Neutrophil morphology is modified by treatment with filgrastim (the nonglycosylated form of rhG‐CSF), while it is not affected by lenograstim (the glycosylated type of rhG‐CSF). Little information is available about actin polymerization in neutrophils from subjects treated with the two types of rhG‐CSF. In the current paper we evaluated two groups of donors of peripheral blood stem cells (PBSC) for allogeneic transplantation. Ten subjects were treated with filgrastim and 10 with lenograstim to mobilize PBSC; 15 blood donors were evaluated as a control group. Actin polymerization (both spontaneous and fMLP‐stimulated) was studied by a flow cytometric assay. A microscopic fluorescent assay was also carried out to evaluate F‐actin distribution in neutrophils. We found that filgrastim induced an increased F‐actin content in resting neutrophils, along with morphologic evidence for increased actin polymerization distributed principally at the cell membrane and frequently polarized in focal areas; in addition, fMLP was not able to induce further actin polymerization. On the contrary, treatment with lenograstim was associated with F‐actin content, distribution, and polymerization kinetics indistinguishable from those displayed by control neutrophils. Such experimental results show that filgrastim and lenograstim display divergent effects also on neutrophil actin polymerization and provide further explanation for previous experimental findings. Am. J. Hematol. 81:318–323, 2006. © 2006 Wiley‐Liss, Inc.